2018
DOI: 10.14738/assrj.52.4114
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Lavender Aromatherapy in Changing Blood Pressure in Middle Age With Primary Hypertension in Mojokerto Regency of East Java Province

Abstract: Background: In 2010, hypertension case becomes one out of 10 most prevalent diseases in Indonesia with prevalence of 8.24%: 3.49% in male and 4.75% in female [8]. The objective of research was to analyze the effectiveness of lavender aromatherapy in changing blood pressure in middle age with primary hypertension. Method: This research employed Quasi Experiment method with control group time series design. The sample of research consisted of 32 respondents taken using probability sampling with simple random tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
4
Order By: Relevance
“…The massage was applied with 10 drops of lavender oil (5 drops per foot) for 20 minutes: 10 minutes per foot. During the application, 20 techniques, each of which lasts for 30 seconds, were used: (1-2) touching: dorsiflexion to feet and plantar flexion, (3) stretching and relaxing the leg, (4) shaking, (5) compression of the solar plexus, (6) grasping the foot with both hands and making toe shifts, (7) thumb-walking along the metatarsals, (8) vibration with compression, (9) simultaneous circular movements to the soles and top of the feet using the 5 fingers, (10) thumb stroking to the plantar surface of the foot, (11) circular movements around the malleolus and Achilles tendon with the fingers, (12) palmar kneading, (13) rotating to all-of-5 toes, (14) rotation and stretching of each toe, (15) foot and ankle rotations, (16) spinal twist, (17) adduction and abduction, (18) press and slide the knuckles from the thumb side to the little finger, (19) effleurage on the feet, and (20) tapping.…”
Section: Foot Massage Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…The massage was applied with 10 drops of lavender oil (5 drops per foot) for 20 minutes: 10 minutes per foot. During the application, 20 techniques, each of which lasts for 30 seconds, were used: (1-2) touching: dorsiflexion to feet and plantar flexion, (3) stretching and relaxing the leg, (4) shaking, (5) compression of the solar plexus, (6) grasping the foot with both hands and making toe shifts, (7) thumb-walking along the metatarsals, (8) vibration with compression, (9) simultaneous circular movements to the soles and top of the feet using the 5 fingers, (10) thumb stroking to the plantar surface of the foot, (11) circular movements around the malleolus and Achilles tendon with the fingers, (12) palmar kneading, (13) rotating to all-of-5 toes, (14) rotation and stretching of each toe, (15) foot and ankle rotations, (16) spinal twist, (17) adduction and abduction, (18) press and slide the knuckles from the thumb side to the little finger, (19) effleurage on the feet, and (20) tapping.…”
Section: Foot Massage Groupmentioning
confidence: 99%
“…A systematic review of 5 studies reported that aromatherapy was an effective approach regarding stress responses in hypertensives 14. The results of 5 other studies, in which inhalation was conducted, reported significant results in blood pressure,10,15–18 salivary cortisol,17 serum cortisol,16 subjective stress,16 and HR 15,16. A significant lowering effect on systolic and diastolic blood pressure was observed according to the findings of a unique study in which aroma massage was applied 19.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan hasil penelitian Suidah, Murtiyani, Fibriana, Kushayati & Lestari (2018), didapatkan data bahwa setelah dilakukan terapi inhalasi menggunakan aromaterapi lavender selama 10 menit dalam 7 hari dapat menurunkan tekanan darah pada pasien hipertensi. Hal ini disebabkan inhalasi dengan aromaterapi bekerja melalui difusi udara yang menstimulasi sel saraf olfaktorius (Suidah, Murtiyani, Fibriana, Kushayati & Lestari, 2018). Selain itu lavender mengandung bahan linoil acetic dan linalool yang dapat merangsang Hypothalamic Pituitary Axis (HPA) untuk mengeluarkan hormone kortisol dan endorphin sehingga mengurangi aktivitas sistem saraf simpatik dan meningkatkan respons saraf parasimpatis (Suidah, Murtiyani, Fibriana, Kushayati & Lestari, 2018).…”
Section: Hasil Dan Pembahasanunclassified
“…In order to enhance the effectiveness of the therapy of patients with EH, it is proposed to undertake this problem and carry out health programmes aimed at the reduction of stress, and increasing the internal health locus of control [5,79,80]. In order to improve the during 7 days led to the reduction of blood pressure in middle-aged individuals [64]. In other study it was confirmed that lavender oil applied in the form of inhalation leads to a decrease in both state anxiety and trait anxiety, and results in the reduction of blood pressure in patients with myocardial infarction [65].…”
Section: Psychological Aspects Of Observance Of Therapeutic Recommendationsmentioning
confidence: 99%